2014
DOI: 10.1097/tp.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Risk of Donor Quality and Recipient Age

Abstract: Background The Kidney Donor Profile Index (KDPI) is a more precise donor organ quality metric replacing age-based characterization of donor risk. Little prior attention has been paid on the outcomes of lower quality kidneys transplanted into elderly recipients. Although we have previously shown that immunological risks associated with older organs are attenuated by advanced recipient age it remains unknown whether risks associated with lower quality KDPI organs are similarly reduced in older recipients. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“… 19 However, this and other previous studies investigating the impact of KDPI on recipient outcomes have not specifically evaluated differences based on donor and recipient diabetes status. 7 , 19 - 21 This information will allow us to better inform patients of underlying implications of accepting these organs based on the recipients’ risk factors, outside of that information provided by the KDPI alone.…”
Section: Discussionmentioning
confidence: 99%
“… 19 However, this and other previous studies investigating the impact of KDPI on recipient outcomes have not specifically evaluated differences based on donor and recipient diabetes status. 7 , 19 - 21 This information will allow us to better inform patients of underlying implications of accepting these organs based on the recipients’ risk factors, outside of that information provided by the KDPI alone.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of recipient at KT was significantly higher in the high KDPI-KTR group than in in the low KDPI-KTR group. Most elderly candidates received KT from marginal donors because of the benefit of old for old KT and the prevention of death prior to KT during the waiting period for DDKT [30][31][32][33]. Since the presence of DM or HTN can suggest an underlying chronic tissue injury irrespective of allograft function, such donors could be diagnosed with CKD [34].…”
Section: Discussionmentioning
confidence: 99%
“…These analyses would be relevant as prior work has suggested that there may be a significant interaction by recipient characteristics, whereby the effect of KDRI on graft outcomes is less pronounced for older, diabetic, or black recipients. 23 , 24 Procurement kidney biopsies are not routinely performed across transplant centers in Canada; thus, the relevance of incorporating such data into risk prediction is not known.…”
Section: Discussionmentioning
confidence: 99%